Heterosis in sweet sorghum - Gabrielle Maria Romeiro Lombardi; Patricia Cardoso Andrade Navegantes; Carlos Henrique Pereira; Jales Mendes Oliveira Fonseca; Rafael Augusto da Costa Parrella; Fernanda Maria Rodrigues Castro; Mara Jane da Rocha; Daniela Oliveira Ornelas; Adriano Teodoro Bruzi; José Airton Rodrigues Nunes (Pesquisa Agropecuária Brasileira, 2018)
Abstract: The objective of this work was to evaluate the potential per se of male-sterile and fertility-restorer lines of sweet sorghum (Sorghum bicolor), as well as to detail the heterosis manifested for some traits directly or indirectly related to ethanol production, accumulation rate, and predictability. Evaluations were performed for 20 genotypes, of which 4 are fertility-restorer lines (R), 3 are male-sterile lines (A), and 12 are experimental hybrids (H) resulting from the partial diallel cross between lines A and R, besides a commercial hybrid CV198 used as a check, in four harvest seasons. The experiments were carried out in the municipalities of Lavras and Sete Lagoas, in the state of Minas Gerais, Brazil. The measured traits were plant height, green mass production, juice extraction, total soluble solids content, and megagrams of Brix per hectare. The male-sterile A1 and the fertility-restorer R1 and R3 lines show the best potential per se, considering all traits and their accumulation rate and predictability over harvest times. Heterosis is significant for all traits. The H11, H13, H14, H21, H22, and H33 hybrids are promising because of their better performance per se and higher heterosis.